In vitro Antimicrobial Studies of Some Pyrazolones and Their SAR Studies - Nathani, Veena; Arora, Kishor (Asian Journal of Chemistry, 2012)
In vitro antimicrobial viz., antifungal studies of some selective pyrazolones on the certified pure cultures of some specified pathogens were carried out. Compounds were established on the basis of analytical methods and advanced spectroscopic techniques. Theoretical semi-empirical studies of these compounds were also carried out. The SAR studies involving lab activities and properties obtained on semi-empirical studies were also done. Two compounds viz., 4-amino antipyrine (C4), 3-methyl-4-nitroso-5-pyrazolone (C5) recorded significant antimicrobial activity against Alternaria solani.